Seismic Fragility Analysis of Institutional Building of Pokhara University - Ghimire, Narayan; Chaulagain, Hemchandra (Himalayan Journal of Applied Science and Engineering, 2020)
Fragility curves are derived from fragility function that indicates the probability of damage of structure due to earthquake as a function of ground motion parameter. It helps to predict the level of structural damage and consequently reduce the seismic risk in specific ground motion. In this scenario, this study is focused on the construction of fragility curve of institutional reinforced concrete (RC) building of Pokhara University. For this, the building of School of Health and Allied Science (SHAS) is considered as a guiding case study. For the numerical analysis, the study building blocks are modelled in finite element-based software. The non-linear static and linear dynamic analyses are employed for numerical analysis. In dynamic analysis, building models are subjected to the synthetic accelerograms of the 2015 Gorkha earthquake. Based on the analyses, the analytical fragility curves are plotted in terms of probability of failure at every 0.1 g interval of peak ground acceleration (PGA) with log normal distribution. Finally, the results are highlighted for different seismic performance level in buildings: slight damage, moderate damage, extensive damage and complete damage for the earthquake of 475 years return period.